Penerapan Model Pembelajaran Talking Stick pada Pembelajaran IPA - Leoni Ambar Valenta; Eka Lokaria; Dedy Firduansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the completeness of science learning outcomes after the Talking Stick Learning Model in Class V Science Learning at SD Negeri 58 Lubuklinggau. This type of research is experimental Research. The research population was all class students at SDN 58 Lubuklinggau City for the 2022/2023 academic year. Sample selection is done by saturated sampling technique. The sample taken was class V.D totaling 23 students and taught with the talkin stick learning model. The research method uses quasi-experiments. Data collection techniques using tests in the form of essay questions. The data obtained were analyzed using the t-test. Based on the results of research and discussion obtained an average value of 81.84 with learning completeness (95.65%). The results of the t-test analysis obtained tcount = 8.08 > ttable = 1.71 which shows that the hypothesis Hₒ is rejected and Hₐ is accepted. So it can be concluded that the learning outcomes of class V students at SD Negeri 58 Lubuklinggau for the 2022/2023 academic year after applying the talkin stick learning model were in the complete significant category. Keywords: Talking Stick, Learning Outcomes, Science.